Nutrient Loss and Economic Loss Due to Sedimentation in Mamasa Sub-Watershed - Nur Isra; Christopaul Pala’langan Toding Layuk (Poltanesa, 2025)
The Mamasa Subwatershed in Indonesia faces significant challenges due to soil degradation, characterized by high erosion and sedimentation rates, leading to nutrient and economic losses. This study analyzes the impact of these issues on nutrient loss and associated economic costs, focusing on nitrogen (N), phosphorus (P), and potassium (K). Sediment samples were collected from upstream, middle, and downstream areas, revealing that the upstream region experiences the highest sedimentation (6,716.21 tons/ha/year) and nutrient losses (94.02 kg N, 12.63 kg P, and 22.16 kg K per hectare annually). Economic losses due to nutrient depletion, calculated using the replacement cost of fertilizers, are estimated at IDR 4.5 billion annually for subsidized fertilizers and IDR 23.7 billion for non-subsidized fertilizers. Key contributing factors include steep slopes (25-45% and >45%), shifting cultivation, and inadequate conservation practices. This degradation significantly impacts soil fertility, reducing agricultural productivity and imposing financial burdens on farmers. The study highlights the need for integrated watershed management, emphasizing soil conservation techniques such as terracing, agroforestry, and farmer education on sustainable practices. These measures could mitigate erosion, reduce nutrient loss, and enhance soil recovery, contributing to the sustainability of the Mamasa Sub-watershed ecosystem and improving local livelihoods. This research underscores the critical need for data-driven, multidisciplinary approaches to address watershed management's ecological, economic, and social dimensions. By implementing effective strategies, stakeholders can achieve more sustainable land use and mitigate the adverse effects of soil degradation.